O discurso da professora pedagoga sobre sua atuação na implementação da formação continuada em colégios do núcleo regional de educação de Pato Branco - PR - Stanqueviski, Eydie Luciana Miglioranza (2022)
The goal of this study consists in the identification of the objectives and competing activities that the pedagogue teacher faces in their work context to conduct the continuing education process. By means of the language, we sought to analyze the working conditions of the pedagogue teacher in the performance of their function, in face of this action. The methodology used was the qualitative and quantitative approach, through bibliographic study and data analysis. These analyzed data were obtained through a questionnaire which, due to the pandemic moment we are going through, was done fully online. The respondents are pedagogue teachers from the education network of the State of Paraná, who work in public schools in the municipalities belonging to the Regional Education Nucleus of Pato Branco. These municipalities are: Bom Sucesso, Chopinzinho, Clevelândia, Coronel Domingos Soares, Coronel Vivida, Honório Serpa, West Itapejara, Mangueirinha, Mariópolis, Palmas, Pato Branco, São João, Saudade do Iguaçu, Sulina and Vitorino. After data production, we carried out an analysis of the statements, seeking to analyze each teacher's answer as an utterance, that is, as a real unit of discursive communication, trying to understand the meanings and ideologies of these discourses and identifying the subjects that were being interviewed; since according to Bakhtin (2003), communication takes place through language, and this is the instrument of mediation between man and nature and among human beings. Through the analysis of the language of the pedagogue teacher, we seek to understand the problem that motivated this research: What the consequences and influences of the diversity of actions that this professional performs within the school bring to the actions of implementation of continuing education with teachers? Another issue that shows up as a point of attention is the lack of continuing education specifically offered to the pedagogue; which, according to our respondents, makes it difficult to help the teachers with regard to the process of implementing actions related to continuing education and, consequently, to the teaching and learning process. Through the results obtained in this study, we noticed that the pedagogues have full awareness of their responsibility regarding the actions that involve the continuing education, as well as its importance and necessity. However, they report some weaknesses, such as lack of theoretical and methodological preparation or mastery so this action can be materialized and they can help in the implementation of actions related to the continuing education. We hope it can contribute to the Regional Education Core, to managers of educational institutions and to the respondents, in order to promote reflections on the work and on the mediating function of the continuing education process. We estimate that, at the end, it will allow us to also contribute to the professional qualification of the pedagogue teachers.